Research on the Design of Hardware-in-loop Simulation Platform for Micro-grid - CHEN Tiancheng (Kongzhi Yu Xinxi Jishu)
It presented the constitution of hardware-in-loop simulation platform for micro-grid and set up such a platform based on dSPACE. A small power converter was designed and the dSPACE simulation platform was also established based on micro-grid converter control strategy. Test results show the validation of research on this platform for micro-grid system.